DRAMATISME DALAM STRATEGI PENUANGAN GAGASAN MELALUI STREET ART KOMUNITAS VISUAL GRAFIS - Widagdo, Muhammad Bayu (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2016)
Like a real-life drama, street art activity is not only understood than mere actualization. Their activities can also be understood as a process of idea communicating, the need for acceptance of communal / community, as well as his message can be received by the community well. To that end, as well as the stage play, they play the role / each character to achieve its objectives in the activities of street art. What stronger motivation behind their characters in Dramatism of strategy in ideas pouring through the street art is an interesting thing to be understood by using the pentad analysis - Kenneth Burke. Pentad analysis outlines the five aspects of human behavior that act, agent, scene, agency, and purpose, like the drama in real life. This study reveals that the motivation behind the idea of pouring through the activities of street art which they do, the other to have the support of people in their community environment, support from the community, as well as social criticism as a reflection of the circumstances surrounding them. In addition, the industry is also strong motive coloring their activities although indirectly.